Aspecto de los pueblos creados y diseñados por los españoles en Pagasinan, Filipinas, a finales del siglo XIX - Albarrán González, Benigno (Estudios humanísticos. Geografía, historia y arte, 1991)
The settlement of the inhabitants who were scattered widely in barangays over the region of Pangasinan, in the Philippines, made it extremely difficult for the Spaniards to christianize the natives. The first task, then, of the missionaries was to draw the converts away from their places to form new towns. To carry out mis work they had to find suitable places for the new settlements. It was the way the towns came into being in Pangasinan, as well as in other territories in the Philippine Islands. In every town founded, the Spaniards designed the streets together with the squares. They also planned the houses for each family. Simultaneously provincial and local rulers were established, whether by appointment or elections, following the pattern already used in Europe.